Asbab Al-Wurud Al-Hadis (Terhadap Asbab Al-Wurud Al-Hadis tentang Potong Tangan) - Qayyum, Rahman (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
To be fair in a variety of activities in the social life is an absolute must for the creation of peace and harmony, so that the order be fair and equitable set by law is not related to the position, descent, race, ethnicity or kinship someone. Because they are weak such as orphans, it must also be acknowledged and treated fairly. Commands to be fair, was also strongly emphasized, either when acting as a judge who will decide the law or when acting as a witness.